2018
DOI: 10.1002/anie.201805927
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalysis for the Umpolung Trifluoromethylthiolation of Tertiary Ethers

Abstract: The first transition-metal-free, site-specific umpolung trifluoromethylthiolation of tertiary alkyl ethers has been developed, achieving the challenging tertiary C(sp )-SCF coupling under redox-neutral conditions. The synergism of organophotocatalyst 4CzIPN and BINOL-based phosphorothiols can site-selectively cleave tertiary sp C(sp )-O ether bonds in complex molecules initiated by a polarity-matching hydrogen-atom-transfer (HAT) event. The incorporation of several competing benzylic and methine C(sp )-H bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 99 publications
2
45
0
2
Order By: Relevance
“…In particular, the radical transformation of alcohols has gained much attention in recent years. To date, great achievements have been made in using alcohols or their derivatives, such as xanthate, oxalate, benzoate, phosphate, and ethers as alkylation agents. MacMillan and co‐workers reported an elegant Minisci reaction under photoredox catalysis with simple alcohols as alkylation agents (Scheme , reaction I a) .…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the radical transformation of alcohols has gained much attention in recent years. To date, great achievements have been made in using alcohols or their derivatives, such as xanthate, oxalate, benzoate, phosphate, and ethers as alkylation agents. MacMillan and co‐workers reported an elegant Minisci reaction under photoredox catalysis with simple alcohols as alkylation agents (Scheme , reaction I a) .…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, Xie, Zhu, and co‐workers reported on the dual photoredox thiocatalytic deoxygenative trifluorothiolation of MOM ethers . On the basis of these studies, the same research group recently disclosed a defunctionalization reaction that was closely related to the work of Wallentin and co‐workers and Nicewicz and co‐workers, namely, the dual photoredox thiocatalytic reduction of simple aliphatic and aromatic carboxylic acids 81 to a broad and diversely functionalized set of deuterated aldehydes 85 (45–92 % yield, Scheme ) …”
Section: Defunctionalizationsmentioning
confidence: 99%
“…Defunctionalization reactions,s uch as (hydro)decarboxylations, [55] deoxygenations, [56] and dehydrogenations, [57] constitute another methodologically important subcategory in the realm of SET-enabled chalcogen multicatalysis.Although this branch of research is not as broadly developed as the majority of those discussed above,l atest discoveries have notably foreshadowed the promising future potential of this reaction class.F or example,W allentin and co-workers demonstrated that the ternary catalytic combination of Fukuzumi salt 62 (R 2 = Me;Ar= mesityl), bis(4-chlorophenyl) disulfide (86), and lutidine (85)c an be employed in the hydrodecarboxylation of ab road panoply of a-amino-, a-hydroxy,a nd phenylacetic acids (Scheme 15). [55a] Under optimized conditions,t he resulting hydrodecarboxylation products 84 were obtained in predominantly good to excellent yields (34-99 %) and with good functional-group tolerance.T he reaction was proposed to involve an initial deprotonation of carboxylic acid 81 by the Brønsted-base catalyst 85,f ollowed by aS ET from the resulting carboxylate ion to the excited photocatalyst 62*.L oss of CO 2 then gives rise to carbon-centered radical 83,which undergoes aHAT event with sulfur catalyst 86.Restoration of catalyst 62 was proposed to occur through an ET/PT sequence analogous to that depicted in Scheme 11.…”
Section: Defunctionalizationsmentioning
confidence: 99%
“…2018 berichteten Xie, Zhu und Mitarbeitende über ein dualkatalytisches Verfahren zur deoxygenierenden Trifluormethylsulfenylierung von MOM‐Ethern . Auf Grundlage dieser Vorarbeiten entwickelte dieselbe Forschungsgruppe eine Methode zur Reduktion von aliphatischen und aromatischen Carbonsäuren 81 zu den entsprechenden Aldehyden 85 .…”
Section: Defunktionalisierungenunclassified
“…[53] Dieses Szenario wird auch durch Berichte über artverwandte Dimerisierungsreaktionen von Chalkogen-Radikalkationen gestützt. [55] [56] Deoxygenierungen [57] und Dehydrierungen, [58]…”
Section: Angewandte Chemieunclassified